Assessment of Hepatic Function, Operative Candidacy, and Medical Management after Liver Resection in the Patient with Underlying Liver Disease - Wagener, Gebhard (Seminars in Liver Disease, 2013)
Liver resection in patients with underlying liver disease remains a formidable challenge. It requires adequate patient selection, a precise surgical plan, and avoidance of additional ischemic insults during surgery. Precise estimation of the residual liver volume using computed tomography or magnetic resonance imaging and computer-assisted volumetry allows the calculation of residual to total liver volume (RLV/TLV) ratios. Although RLV/TLV ratios over 20 to 25% are considered sufficient in healthy livers, patients with cirrhosis may only tolerate resections that result in RLV/TLV ratios over 40% and higher. Conventional laboratory tests may not be able to sufficiently predict liver reserve after resection. Dynamic tests such as indocyanine green clearance have been used to assess residual liver function and assist in deciding about operability of patients with underlying liver disease undergoing extensive resections. Intraoperative management should focus on avoiding blood loss and ischemic injury to the liver. Low central venous pressure may reduce blood loss and is recommended if tolerated without impeding renal perfusion. Portal vein and hepatic artery occlusion during resection can reduce blood loss, but will cause ischemic insult to the liver that may jeopardize residual liver function and induce postoperative hepatic failure. When feasible, vascular occlusion should be avoided in patients with underlying liver disease. The postoperative recovery is usually fast if sufficient liver remains. However, vigilance is required to detect liver dysfunction and treat its complications.
Keywords: hepatectomy; liver function; cirrhosis; liver tumors; dynamic liver tests; liver injury